SOCIO-ECOLOGICAL DYNAMICS AND LOCAL WISDOM TOWARD ADAPTIVE CAPABILITY TO USE AGRICULTURAL TECHNOLOGY BY THE COMMUNITY OF KASEPUHAN SINAR RESMI - sri rahayu pudjiastuti (Fakultas Seni Rupa dan Desain ITB, 2021)
The obligation to maintain and preserve the environment, in the view of all religions and beliefs, is a must for thecommunity so that religious values and local wisdom of the community also become binding provisions to maintainand preserve the environment. This study aims to describe, analyze, and solve problems regarding socio-ecologicaldynamics and local wisdom about the adaptability of using technology in the community of Kasepuhan Sinar Resmi.This study uses a descriptive-analysis method which is to describe the analysis and discuss it comprehensively andintegrally. Data collection techniques were carried out through interviews and literature review. This study foundthat the community’s local wisdom based on its adaptability to use agricultural technology at the Community ofKasepuhan Sinar Resmi is related to environmental preservation and the effort to make the environment useful for life